2006
DOI: 10.1111/j.1540-6261.2006.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cross‐Section of Volatility and Expected Returns

Abstract: We examine the pricing of aggregate volatility risk in the cross-section of stock returns. Consistent with theory, we find that stocks with high sensitivities to innovations in aggregate volatility have low average returns. Stocks with high idiosyncratic volatility relative to the French (1993, Journal of Financial Economics 25, 2349) model have abysmally low average returns. This phenomenon cannot be explained by exposure to aggregate volatility risk. Size, book-to-market, momentum, and liquidity effects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

208
2,180
45
18

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,959 publications
(2,451 citation statements)
references
References 74 publications
208
2,180
45
18
Order By: Relevance
“…Rubinstein (1973), Kraus and Litzenberger (1976), Hwang and Satchell (1999) and Ranaldo and Favre (2003) noted that when the market returns are not normal (but skewed or leptokurtic),the standard CAPM is not enough to price equity returns and they recommended for the addition of higher moments (skewness or kurtosis). Very recently, Ang, Chen and Xing (2006), Ang, Hodrick, Xing and Zhang (2006) and Xing, Zhang and Zhao (2010) suggested that the asymmetry of the returns distribution is important for asset pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Rubinstein (1973), Kraus and Litzenberger (1976), Hwang and Satchell (1999) and Ranaldo and Favre (2003) noted that when the market returns are not normal (but skewed or leptokurtic),the standard CAPM is not enough to price equity returns and they recommended for the addition of higher moments (skewness or kurtosis). Very recently, Ang, Chen and Xing (2006), Ang, Hodrick, Xing and Zhang (2006) and Xing, Zhang and Zhao (2010) suggested that the asymmetry of the returns distribution is important for asset pricing.…”
Section: Introductionmentioning
confidence: 99%
“…An unsystematic risk is specific to an individual company. It is measured by the residual variance inventory in a given period using the error terms acquired from a standard asset pricing model such as the Fama-French three-factor model or the CAPM (see Ang, Hodrick, Xing and Zhang, 2006). Therefore, the unsystematic risk is represented as firm specific risk.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, from the above critical review , one can observe that at the level of the relationship between unsystematic risks fluctuations and stocks expected returns, the studies' results were subdivided into three different scenarios: first, studies proved negative relationship between unsystematic risks and returns, like study of Ang et al (2006) Second scenario is represented by some studies that proved a positive relationship between unsystematic risks and returns like, study of Goyal and Santa Clara (2003) jiang and Lee (2006) as both studies applied to the U.S , on the aggregate level,.Also the same results were reached by Fu (2009) and Malkiel and Xu (2003) but at the firm level. And finally studies proved non statistical significant relationship between unsystematic risks and returns, such as, study of Bali and Cakici (2008), applied to the U.S as different fluctuations scales were used by using daily and monthly data from July 1926 to December 2002.…”
Section: Angelidis (2010) Applied On 24 Countries Of Ecms Incorporatementioning
confidence: 99%
“…Jegadeesh and Titman (1993) show that buying stocks that performed well in the past generate significant outperformance over the broad index. Ang et al (2006) and Li et al (2016) find that stocks with high idiosyncratic volatility have low average returns.…”
Section: Introductionmentioning
confidence: 99%